2022
DOI: 10.1371/journal.pone.0278381
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mortality of hospitalized facial trauma patients in Al-Ain City, United Arab Emirates

Abstract: Background Facial injuries affect one-third of severely injured patients. These injuries have devastating long-term negative impacts on quality of life. We aimed to study the epidemiology of facial injuries and factors affecting the mortality of hospitalized facial trauma patients in Al-Ain City, United Arab Emirates. Methodology This is a retrospective analysis of prospectively collected data from Al-Ain Hospital Trauma Registry. All patients with facial injury who were hospitalized for more than 24 hours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Similarly, since men predominantly undertake driving roles, they are at a higher risk of RTIs. A literature search also revealed that injury-specific deaths are more common in males than females [ 25 ]. Results of the current study suggest that injury-specific deaths were highest in the age group 25-34 years and 35-54 years.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, since men predominantly undertake driving roles, they are at a higher risk of RTIs. A literature search also revealed that injury-specific deaths are more common in males than females [ 25 ]. Results of the current study suggest that injury-specific deaths were highest in the age group 25-34 years and 35-54 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, our figure for the overall median length of hospital stay was lower than that reported by other studies on camel-related injuries [ 5 , 18 ]. Studies have shown that the most reliable predicting factors for mortality among patients with facial injuries were advanced age, increased ISS, and low GCS [ 25 , 29 , 30 ]. Our patients had a good overall outcome with no reported mortality.…”
Section: Discussionmentioning
confidence: 99%